2023
DOI: 10.1038/s41467-023-37044-4
|View full text |Cite
|
Sign up to set email alerts
|

Lateral hypothalamic leptin receptor neurons drive hunger-gated food-seeking and consummatory behaviours in male mice

Abstract: For survival, it is crucial for eating behaviours to be sequenced through two distinct seeking and consummatory phases. Heterogeneous lateral hypothalamus (LH) neurons are known to regulate motivated behaviours, yet which subpopulation drives food seeking and consummatory behaviours have not been fully addressed. Here, in male mice, fibre photometry recordings demonstrated that LH leptin receptor (LepR) neurons are correlated explicitly in both voluntary seeking and consummatory behaviours. Further, micro-endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Previous studies have not fully accounted for the multitude of dynamic events that can influence the activity of LH LepR neurons ( 39, 50 ). Past fragmented studies demonstrated that LH LepR neurons reinforce lever pressing, possess rewarding properties ( 50 ), and initiation of seeking or consummatory behaviours for food ( 38 ). In our experimental paradigm, LH LepR neural activity increased at accessibility moment and decreased at inaccessibility moment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have not fully accounted for the multitude of dynamic events that can influence the activity of LH LepR neurons ( 39, 50 ). Past fragmented studies demonstrated that LH LepR neurons reinforce lever pressing, possess rewarding properties ( 50 ), and initiation of seeking or consummatory behaviours for food ( 38 ). In our experimental paradigm, LH LepR neural activity increased at accessibility moment and decreased at inaccessibility moment.…”
Section: Discussionmentioning
confidence: 99%
“…A shelter was placed and an electrical shock was given as punishment in a square chamber, as previously reported ( 38 ). All reward-associated cues (e.g., visual or sound cues) were eliminated to measure voluntary seeking behaviour initiation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations